The Impact of e-NPQEL on the Continuance Intention of Using e-Training among Aspired School Leaders in Malaysia - Ismail, Aziah; Zaharuddin, Rozniza; Hashim, Noor Hashimah; Ariffin, Joohari (International Journal of Interactive Mobile Technologies (iJIM), 2020)
Information and communication technology (ICT) has become an important platform for e-training as it offers many advantages in providing new knowledge and skills for professional development. This study aims to examine the impact of e-NPQEL on the continuance intention of using online learning among aspired school leaders in Malaysia. From the data analysis, results revealed the features of e-NPQEL that influence the perceived usefulness of the participants on the program and the mediating effect of this aspect on the relationship between e-NPQEL features and continuance intention. The results of this study imply to the Human Resource managers that intend to have e-training for their professional development agendas.